Prevalence of sarcopenia in patients with COPD through different musculature measurements: An updated meta-analysis and meta-regression - Jie He; Jie He; Hezhi Li; Hezhi Li; Jun Yao; Jun Yao; Yan Wang; Yan Wang (Frontiers in Nutrition, 2023)
AimChronic obstructive pulmonary disease (COPD) patients vary widely in terms of the prevalence of sarcopenia, which is partially attributed to differences in diagnostic criteria and disease severity. There are several different musculature measurements that are used to quantify sarcopenia. This study included published literature for meta-analysis to assess the sarcopenia prevalence in COPD patients and correlate the disease with the clinical characteristics of such patients.MethodsA comprehensive review of the English and Chinese literature on sarcopenia prevalence in COPD patients was conducted using electronic databases such as China National Knowledge Infrastructure (CNKI), Web of Science, Cochrane Library, EMBASE, PubMed, and Wanfang. Two researchers analyzed the studies for Newcastle-Ottawa Scale. The software Stata 11.0 was employed for the analysis of the acquired data. The standard mean differences method was utilized for the estimation and quantification of the effect size. Furthermore, a fixed- or random-effects model was employed for conducting a combined analysis.ResultsIn total, 56 studies were included as per the specific inclusion criteria. The resulting data of the assessed COPD patients in this research indicated a 27% prevalence of sarcopenia. Further analysis of subgroups was executed per disease severity, ethnicity, diagnostic criteria, gender, and age. Per these findings, increased disease severity elevated the prevalence of sarcopenia. The Latin American and Caucasian populations indicated an increased prevalence of sarcopenia. In addition, the prevalence of sarcopenia was related to diagnostic criteria and definition. Male COPD patients had a higher prevalence of sarcopenia than female COPD patients. COPD patients with an average age greater than 65 had a slightly higher prevalence of sarcopenia. COPD patients with comorbid sarcopenia had poorer pulmonary function, activity tolerance, and clinical symptoms than patients with COPD alone.ConclusionSarcopenia prevalence is high (27%) in COPD patients. In addition, these patients had worse pulmonary function and activity tolerance compared to patients without sarcopenia.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=367422, identifier CRD42022367422.